THE EMERGENCE OF TRAGEDY AND COMEDY IN LIFE AND ART (Academia Science Repository, 2023)
Aesthetically evaluating phenomena, a person determines the measure of his dominance over the world. This measure depends on the level and nature of the development of society, its production. The latter reveals one or another meaning for a person of the natural properties of objects, determines their aesthetic properties. This explains that the aesthetic manifests itself in different forms: beautiful, ugly, sublime, base, tragic, comic, etc.